PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS V SDIT AL-MADINAH CIBINONG - Mulyasari, R. Dina; Asmahasanah, Salati; Arif, Suyud (Program Studi PGMI, 2019)
This research is tofind out the application of problem based learning to the learning outcomes of students in grade V SDIT Al-Madinah Cibinong. This study is a classroom action research type of classroom action research. Data collection techniques using research instruments, namely observation, interviews, tests and documentation. This study produced data on student learning outcomes in social studies subjects in the 5th grade of SDIT Al-Madinah before being applied to PTK only achieving completeness 60,7% with an average value of 64,6. Students who reach the KKM standard are only 11 students while those that have not reached as many as 17 students. In the first cycle, student reached the minimum standard were 15 students, while those that had not reached the minimum standard scorewere 13 students with an average score of 72 with learning completeness of 53,6%. Whereas in the second cycle, the number of students who reached the minimum standard score were 24 students and students who had not reached the minimum standard score standard were 4 students with an average score of 83,4 and the level of completeness was 85,7%. Then it can be concluded that there is a significant effect on the application of the problem based learning model to student learning outcomes.